No connection between the Yangtze and Red rivers since the late Eocene - Zhang, Zengjie; Daly, J. Stephen; Yan, Yi; Lei, Chao; Badenszki, Eszter; Sun, Xilin; Tian, Yuntao (Marine and petroleum geology, 2021)
The unusual drainage pattern in the southeastern Tibetan Plateau has been proposed to result from the breakup of a single paleo-Red River system. However, whether there or not was a major early Cenozoic “paleo-Red River” flowing from southeastern Tibet to the South China Sea is still highly debated. In this study, we have used Pb isotopic analyses of detrital K-feldspar to constrain the sedimentary provenance of the Cenozoic deposits from the onshore Jianchuan Basin and offshore Yinggehai and Qiongdongnan basins, and further to decipher the drainage evolution of the upper-middle Yangtze and Red Rivers. Detrital K-feldspar from the Baoxiangsi Formation in the Jianchuan Basin shows an apparent mixture of sand delivery from both the upper Yangtze and Yalong rivers, indicating that there was a river draining the Qiangtang Block and Songpan-Ganzi that used to flow through the Jianchuan Basin during the Eocene. In contrast, K-feldspar Pb isotopes from the Eocene to Pliocene deposits of the Yinggehai and Qiongdongnan basins are different from those of the Jianchun Basin and Yangtze, Salween, and Mekong rivers, but similar to that of the modern Red River. These lines of evidence suggest that major rivers draining southeastern Tibet have not been tributaries of the paleo-Red River and hence, there has been no fluvial connection between southeastern Tibet and the South China Sea since at least the late Eocene. •Sedimentary provenance of the Jianchuan,Yinggehai and Qiongdongnan basins were constrained by Pb-in-K-feldspar.•There was a river draining the Qiangtang and Songpan-Ganzi that used to flow through the Jianchuan Basin during the Eocene.•Sedimentary provenance of the YGHB and QDNB has been similar to the modern Red River since the late Eocene.•No fluvial connection between southeastern Tibet and the South China Sea since at least the late Eocene.